Emerging Insights on Brazilian Pepper Tree (Schinus terebinthifolius) Invasion: The Potential Role of Soil Microorganisms - Dawkins, Karim; Esiobu, Nwadiuto (Frontiers in Plant Science, 2016)
Invasive plant species constitute a major ecological and economic problem worldwide, often distorting trophic levels and ecosystem balance. Numerous studies implicate factors ranging from environmental plasticity, competition for nutrient and space, and allelopathy in the success of invasive species in general. The Brazilian Pepper tree (BP) was introduced to the United States in the 1800s and has since become a category one invasive plant in Florida. It has aggressively spread to about 3000 km2 of terrestrial surface, fueled in part by the prevalence of the hybrid genotypes and environmental perturbations. It displays some of the well-established invasive mechanisms but there is a serious dearth of knowledge on the plant-microbe-soil interactions and whether the rhizobiome plays any roles in the displacement of native flora and the range expansion of BP. Several control measures, including chemical, mechanical and biological antagonism have been used with limited success while restoration of natives in soils from which BP was removed has proved problematic partly due to a poorly understood phenomenon described as the “BP legacy effect”. Emerging evidence suggests that allelopathy, selective recruitment of beneficial soil microbes, disruption of microbial community structure and alteration of nutrient cycling, exhibited by many other invasive plant species may also be involved in the case of BP. This brief review discusses the well-established BP invasion mechanisms and highlights the current understanding of the molecular, below-ground processes. It also points out the gaps in studies on the potential role of microbial interactions in the success of BP invasion. These hitherto poorly studied mechanisms could further explain the aggressive spread of BP and could potentially contribute significantly to effective control measures and enable appropriate strategies for restoring native plants. The review advocates for the use of cutting-edge techniques in advancing the plant microbiome science. Ultimately, comparing metagenomic analyses of the rhizobiome of invasive plants grown in native and non-native soils could lead to a better understanding of the microbial determinants of biotic resistance, potentially empowering environmental managers with some predictive power of future trends of plant invasion.